Culture et politique dans la revendication régionale contemporaine :lllustrations corses et interprétations - Christophe Roux (Lengas)
This article offers a reflection onto the way cultural and political claims are articulated in the discourse of regional minorities in France. It is based on the case of Corsica where political claims are prominent and encompass all other aspects after 1945 while the pre-war era was characterized, instead, of a sort of cultural production of politics by a journal such as A Tramuntana and a manifest such as the one included in A Cispra. Those variations are interpreted within the sequential analytical framework proposed by Miroslav Hroch.